The performance of Leland's option pricing models in the presence of transaction costs: evidence from the Australian index option market - Abdullah, Mimi Hafizah; Li, Steven (2010)
This study examines the performance of a few option pricing models with transaction costs in valuing call options on S&P/ASX 200 index. The option pricing models of the original Leland model as well as its two variations are tested and contrasted with the Black-Scholes-Merton (BSM) model across moneyness and maturity. Our empirical results reveal that the two variations of the original Leland model appear to perform well in pricing call options except short-term out-of-the-money calls. The pricing performance of Leland models appears to improve as rebalance becomes more frequent (from quarterly to daily) except for short-term and medium-term out-of-the-money calls. Moreover, the prices generated from the Leland models are subject to fewer and weaker pricing biases than are the prices from the BSM model. Overall, this paper demonstrates that it is important to consider transaction costs in option pricing that may lead to a more effective pricing of call options.